Relationship Between School Discipline Culture with Student Learning Motivation - Nurmawati, Nurmawati; Falentino, Zidan (Jurnal Aplikasi IPTEK Indonesia, 2024)
The study aims to discover and describe the cultural relationships of school disciplines with students’ learning motivations at school. The approach used in this study is computational research with Correlational descriptive methods. The population in the study was 164 students with a sample of 117 students. Sampling techniques are based on proportional random sampling. The instrument used is the likert model scale on the cultural variables of discipline and learning motivation. Data analysis techniques use Pearson product moment analysis using SPSS version 26. The results of the study showed that the level of culture of the discipline of the school is in the high category, the degree of student learning motivation in the higher category and there is a positive and significant relationship between the culture of school discipline with the motivation of students to learn in the school